2014
DOI: 10.33762/bvetr.2014.98806
|View full text |Cite
|
Sign up to set email alerts
|

Using Two Different Promoters of Lysostaphin Gene to Change Protein Production

Abstract: Bacteriocins are bacterial antimicrobial peptides with bactericidal activity against other bacteria. Staphylococcins are bacteriocins produced by staphylococci, which are gram-positive bacteria with medical and veterinary importance. In this study we are using two promoters from two plasmids to lysostaphin gene to change production of lysostaphin protein then killed Staphylococcus aureus and compared with pBluescript plasmid as control, pTrc99a get increased the production of lysostaphin protein while the pBAD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
0
1
Order By: Relevance
“…The result of the present study showed that limited increasing in concentration of lysostaphin protein when used pET-32a(+) plasmid compared with other study (25), which recorded less then concentration of lysostaphin protein with other plasmid, this study recorded lysostaphin concentration from pTrc99a plasmid 1.012mg/ml which less than our study 1.113 mg/ml, as well as 0.622 mg/ml concentration by used pBAD30 plasmid.…”
Section: Discussioncontrasting
confidence: 67%
“…The result of the present study showed that limited increasing in concentration of lysostaphin protein when used pET-32a(+) plasmid compared with other study (25), which recorded less then concentration of lysostaphin protein with other plasmid, this study recorded lysostaphin concentration from pTrc99a plasmid 1.012mg/ml which less than our study 1.113 mg/ml, as well as 0.622 mg/ml concentration by used pBAD30 plasmid.…”
Section: Discussioncontrasting
confidence: 67%